Wind erosion processes and related glyphosate transport in the loess pampean region of Córdoba province, Argentina - Bento, Célia; Geissen, Violette; Riksen, Michel; Mol, Hans; Murialdo, Raquel; Ritsema, Coen; Reyna, Santiago (2022)
Fil: Bento, Célia P. M. Wageningen University. Soil Physics and Land Management; Países Bajos.